2019
DOI: 10.3341/kjo.2019.0060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Protective Effect of an Ophthalmic Viscosurgical Device on the Ocular Surface in Dry Eye Patients during Cataract Surgery

Abstract: Purpose: To evaluate the protective effect of applying an ophthalmic viscosurgical device (OVD) to the ocular surface during cataract surgery and its ability to prevent dry eye syndrome. Methods: Twenty-four patients aged 50 to 75 years who underwent cataract surgery at Seoul National University Bundang Hospital and agreed to participate in the study were included and divided into two groups: a study group who underwent cataract surgery after application of an OVD to the ocular surface, and a control group who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Likewise, Yoon et al. 74 in a comparative prospective study of 24 patients, reported the use of an ophthalmic visco-surgical device (OVD) (DisCoVisc, Alcon Laboratories, Inc.) intra-operatively to coat the ocular surface and found significant improvements in TBUT, OSDI scores and ocular surface staining scores at 1 week post-surgery. These improved outcomes with ocular surface coating with OVDs are supported by the studies of Oh et al.…”
Section: The Pathophysiology Of Cataract Surgery Associated Dedmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, Yoon et al. 74 in a comparative prospective study of 24 patients, reported the use of an ophthalmic visco-surgical device (OVD) (DisCoVisc, Alcon Laboratories, Inc.) intra-operatively to coat the ocular surface and found significant improvements in TBUT, OSDI scores and ocular surface staining scores at 1 week post-surgery. These improved outcomes with ocular surface coating with OVDs are supported by the studies of Oh et al.…”
Section: The Pathophysiology Of Cataract Surgery Associated Dedmentioning
confidence: 99%
“…As discussed above, there are several intra-operative factors that may be important in the pathophysiology of cataract surgery-induced iatrogenic DED including corneal nerve damage secondary to surgical incisions; the potentially toxic effects of povidone-iodine and topical anaesthetic drops on the ocular surface; repeated ocular surface drying/irrigation; phototoxicity; and direct ocular surface trauma. 51 , 55 78 , 83 85 The cataract surgeon needs to be mindful of these factors when operating on patients, especially when a patient has any pre-existing DED 17 , 18 , 47 , 48 , 97 ( Table 1 ).…”
Section: Considerations Of the Management Of Cataract Surgery Associamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recently published study showed that the use of this intracameral solution during cataract surgery could reduce ocular surface inflammation evaluated by in vivo confocal microscopy, assuring a better postoperative tear film stability and visual quality [ 47 ]. A recent report [ 48 ] has also indicated that persistent intraoperative surface irrigation may contribute to immediate postoperative dry eye symptoms. Applying an ophthalmic viscosurgical device (OVD) on the corneal surface during surgery results in less ocular surface damage than balanced salt solution (BSS) irrigation on the surface, providing the advantage of a clear surgical view with no difference in surgical time [ 48 , 49 ].…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…A recent report [ 48 ] has also indicated that persistent intraoperative surface irrigation may contribute to immediate postoperative dry eye symptoms. Applying an ophthalmic viscosurgical device (OVD) on the corneal surface during surgery results in less ocular surface damage than balanced salt solution (BSS) irrigation on the surface, providing the advantage of a clear surgical view with no difference in surgical time [ 48 , 49 ].…”
Section: Intraoperative Managementmentioning
confidence: 99%